Kajian Pengaruh Dosis Biochar Sekam Padi dan Tipe Konteiner Terhadap Beberapa Karakteristik Media dan Pertumbuhan Acacia crassicarpa di Pembibitan - Johan Johan; Aswandi Aswandi; Heri Junedi (Universitas Batanghari, 2023)
One material that has the potential to replace cocopeat and peat for planting media is rice husk biochar because it has the ability to increase pH, has a porous structure and is rich in potassium. Currently, Acacia crassicarpa nurseries generally use polybag and polytube containers which often have negative effects on rooting and problems in the planting process in the field. The use of paper bags as an alternative to containers that have a larger volume advantage than polytubes, and can be directly planted in the field requires a more in-depth study. This study aims to examine the optimum dosage of rice husk biochar and container type for the growth of Acacia crassicarpa seedlings in nurseries. This study used a Split Plot design with a factorial pattern, each consisting of 3 main plots, namely polybag, polytube and paperbag and 4 subplots consisting of 4 doses of husk charcoal biochar, respectively 0%, 10%, 30% and 50 %. Each treatment was repeated 3 times. The variables measured were media porosity, media pH, plant height, stem diameter and seedling root volume. Data were analyzed using the ANOVA test and then tested further with the DNMRT test at α5%. Analysis using SPSS software version 2.3. The results indicated that the interaction between the type of container and the dosage of rice husk biochar only had a significant effect on the porosity variable. The type of container alone did not show a significant effect on soil pH variables, but had a significant effect on plant height, stem diameter and root volume variables. Polybags give the best results for the height and diameter of the seedlings. Polytube gave the best effect on root volume variables, paperbags showed the least circular roots. This variable was not tested but visually shows a significant difference. Treatment of single doses of biochar had a significant effect on soil pH, seedling height, seedling diameter and seedling root volume. There was a tendency to increase soil pH and root volume with increasing doses of biochar. The best seedling height and diameter variables were obtained at a dose of 10% biochar, this gives an indication that the biochar dose is optimum for seedling growth